FWS531: Electronic Media Writing / College of Creative Arts - UiTM, College of Creative Arts (2023)
This course is focusing on the 5W1H of writing articles for screen and digital contents. Each lecture focuses on Electronic Publishing (also referred to as e-publishing or digital publishing or online publishing) that includes the digital publication of e-books, digital magazines, and the development of digital libraries and catalogues. Weekly lecture also includes an editorial aspect, that consists of editing books, journals or magazines that are mostly destined to be read on a screen (computer, e-reader, tablet, smartphone).